Possible Significance of Neutrophil–Hemoglobin Ratio in Differentiating Progressive Supranuclear Palsy from Depression: A Pilot Study - Michał Markiewicz; Natalia Madetko-Alster; Dagmara Otto-Ślusarczyk; Karolina Duszyńska-Wąs; Bartosz Migda; Patryk Chunowski; Marta Struga; Piotr Alster (Diseases)
Background: Research has associated chronic inflammation with the evolution of neurological and psychiatric disorders. Neurodegenerative diseases, including Parkinson’s Disease (PD), Alzheimer’s Disease (AD), and less common ones such as Progressive Supranuclear Palsy (PSP), are commonly linked to depression. However, the pathomechanisms and the role of neuroinflammation in these disorders remain unclear; therefore, interest is increasing in easily accessible inflammatory morphological assessments of blood samples, such as the neutrophil-to-lymphocyte ratio (NLR), the neutrophil-to-monocyte ratio (NMR), and the neutrophil-to-hemoglobin ratio (N/HGBR). Methods: The authors analyzed 15 age-matched controls and 21 patients with PSP; the PSP group was additionally divided into 11 patients without depression (PSP) and 10 with depression (Beck Depression Inventory [BDI] ≥ 14) (PSP-D). Results: In the PSP-D group, the level of N/HGBR was significantly lower than in the controls (p = 0.01), but there were no significant differences in any other neutrophil-derived parameters or comparisons of morphological blood assessment. Patients with PSP-D exhibited a marginally significant decrease in neutrophil levels compared to the controls. Conclusions: This is the first study highlighting the possible significance of peripheral inflammatory factors in patients with PSP affected by depression. It highlights possible tendencies in the area of non-specific inflammatory markers and suggests their relation to affective disorders in PSP.